2009
DOI: 10.1136/jech.2009.087544
|View full text |Cite
|
Sign up to set email alerts
|

A quick self-assessment tool to identify individuals at high risk of type 2 diabetes in the Chinese general population

Abstract: Background Currently available tools for identifying individuals at high risk of type 2 diabetes can be invasive, costly and time consuming. This study aims to develop and validate a self-assessment tool for identifying individuals at high risk of type 2 diabetes in the Chinese general population. Methods A cross-sectional survey was conducted from 2000 to 2001 in a nationally representative sample of 15 540 Chinese adults aged 35e74 years. The diabetes risk level (DRL) was assessed by classification and regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 30 publications
(43 reference statements)
0
36
0
Order By: Relevance
“…Thirteen studies (33%) were published in Diabetes Care , five studies (13%) were published in Diabetes Research and Clinical Practice , four studies (10%) were published in Diabetic Medicine and three studies (8%) were published in the Annals of Internal Medicine . Four studies reported separate risk prediction models for men and women [23-26], thus our review assesses a total of 43 risk prediction models from 39 articles. Thus the denominator is 39 when reference is made to studies and 43 when reference is made to risk prediction models.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen studies (33%) were published in Diabetes Care , five studies (13%) were published in Diabetes Research and Clinical Practice , four studies (10%) were published in Diabetic Medicine and three studies (8%) were published in the Annals of Internal Medicine . Four studies reported separate risk prediction models for men and women [23-26], thus our review assesses a total of 43 risk prediction models from 39 articles. Thus the denominator is 39 when reference is made to studies and 43 when reference is made to risk prediction models.…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes predicted by the models varied because of different definitions of diabetes and patients included (Tables 1, 2 and 3). Seventeen studies (44%) described a model to predict the development of diabetes (incident diabetes) [23,25,27-40], fifteen (38%) described the development of a model to predict the risk of having undiagnosed diabetes [41-53], four described the development of a prediction model for diagnosed and undiagnosed diabetes [24,26,54,55], one described the development of a prediction model for undiagnosed diabetes and prediabetes [56], one described the development of a prediction model for abnormal postchallenge plasma glucose level (defined as ≄ 140 mg/dL) to predict undiagnosed diabetes [57] and one described the development of a model to predict the risk of undiagnosed type 2 diabetes and impaired glucose regulation [58]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The earlier detection of individuals at high risk of T2D is a high priority for primary prevention (Xie et al, 2010). Research protocols for estimating a person's future risk for T2D have depended primarily on identifying IGT through a 2-hour oral glucose tolerance test (Kahn et al, 2009).…”
Section: Introductionmentioning
confidence: 99%